2022
DOI: 10.1177/2333794x221085386
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Pulmonary Computerized Imaging Findings of Critically Ill Egyptian Patients with Multisystem Inflammatory Syndrome in Children

Abstract: Objectives. This study was carried out to delineate the patients’ characteristics and the imaging findings and their relation to some biochemical markers of 31 critically ill patients with MIS-C. Design. A retrospective cross-sectional study including all critically ill MIS-C patients admitted to the PICU from June 23rd to July 22nd, 2020. Results. Eighteen males and 13 females, with a median age of 9 years (interquartile range 6-11) presented mainly with fever (100%) and hypotension (100%). Abnormalities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We primarily explain this by the presence of a co-bacterial infection due to reduced immunity in most of our patients with other comorbidities, but there was no statistically significant difference in consolidation between patients with comorbidities or not. This could be explained that consolidative pattern was significantly higher in moderate and severe groups which represent one-third of our cases, this is consistent with a study done on 31 severe COVID-19 pediatric patients with consolidative patches were the most predominant CT feature [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…We primarily explain this by the presence of a co-bacterial infection due to reduced immunity in most of our patients with other comorbidities, but there was no statistically significant difference in consolidation between patients with comorbidities or not. This could be explained that consolidative pattern was significantly higher in moderate and severe groups which represent one-third of our cases, this is consistent with a study done on 31 severe COVID-19 pediatric patients with consolidative patches were the most predominant CT feature [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Their identification and the volumetric quantification may allow an easier classification in terms of gravity, extent and progression of the disease. Moreover, this may provide a high-impact tool to enhance awareness of the severity of COVID-19 pneumonia [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 represents 47.5% (115/242) of MIS‐C and MIS‐A cases reported in nine published African studies. MIS was more common in men between the ages of 2.3 and 51 years 25–27,67–81 . Polymorphous maculopapular eruptions on the trunk and flexural areas, acral erythema, extremity swelling, desquamation, mucositis, and fissured lips are all examples of MIS dermatological lesions 25–27,67–81 .…”
Section: Clinical Manifestations Of Covid‐19‐related Cutaneous Manife...mentioning
confidence: 99%
“…Several studies in African populations have reported MIS-C and MIS-A or Kawasaki-like disease. [25][26][27][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] published African studies. MIS was more common in men between the ages of 2.3 and 51 years.…”
Section: Clinical Manifestations Of Covid-19-related Cutaneous Manife...mentioning
confidence: 99%
See 1 more Smart Citation